2017
DOI: 10.1242/jcs.196931
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized phagosomal NOX2 complex is replenished from lysosomes

Abstract: In dendritic cells, the NADPH oxidase 2 complex (NOX2) is recruited to the phagosomal membrane during antigen uptake. NOX2 produces reactive oxygen species (ROS) in the lumen of the phagosome that kill ingested pathogens, delay antigen breakdown and alter the peptide repertoire for presentation to T cells. How the integral membrane component of NOX2, cytochrome b558 (which comprises CYBB and CYBA), traffics to phagosomes is incompletely understood. In this study, we show in dendritic cells derived from human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 89 publications
7
47
1
Order By: Relevance
“…The Qa-SNARE Stx7 mainly locates at late endosomes and lysosomes (17,24,62,88,217), but is also found at early and recycling endosomes (29,88,158,247) and the plasma membrane (134,158). In addition, Stx7 locates at phagosomes, as found by imaging (62,79), Western blot (271), and proteomics (38,43,156,286,293). Although Stx7 can be recruited to phagosomes in multiple phases (267), several studies showed a rapid increase in phagosomal Stx7 over time after uptake (Refs.…”
Section: F Stx7mentioning
confidence: 96%
See 3 more Smart Citations
“…The Qa-SNARE Stx7 mainly locates at late endosomes and lysosomes (17,24,62,88,217), but is also found at early and recycling endosomes (29,88,158,247) and the plasma membrane (134,158). In addition, Stx7 locates at phagosomes, as found by imaging (62,79), Western blot (271), and proteomics (38,43,156,286,293). Although Stx7 can be recruited to phagosomes in multiple phases (267), several studies showed a rapid increase in phagosomal Stx7 over time after uptake (Refs.…”
Section: F Stx7mentioning
confidence: 96%
“…The Stx7-Vti1b-Stx8 SNARE complex with VAMP7 (R) instead of VAMP8 mediates fusion of late endosomes with lysosomes and homotypic fusion of lysosomes (251,322). Stx7 also mediates fusion of lysosomes with phagosomes (24,79) and plays a role in trafficking from the trans-Golgi network to endosomes (57).…”
Section: F Stx7mentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymes of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Nox) family are important sources of reactive oxygen species (ROS) (Brandes et al ., ). Phagocytosis‐associated Nox plays a crucial role in host defenses involving neutrophils, monocytes, and macrophages (Dingjan et al ., ; Minakami & Sumimotoa, ). ROS production is mediated by Nox, which transfers electrons to the extracellular space in converting oxygen to O 2 − (Okochi Y et al ., ).…”
Section: X‐ray Spectra Intensity Of Nitrogen Phosphorus and Cerium Ementioning
confidence: 97%